NATURAL DYES EXTRACTED FROM WASTE LEAVES OF TERMINALIA CATAPPA LOCALLY KNOWN AS TROPICAL ALMOND AND ITS APPLICATION ON SILK FABRICS PRETREATED WITH ECO FRIENDLY AND NONECO-FRIENDLY MORDANTS - Vadwala, Yogesh; Kola, Namrita (International Journal of Research -GRANTHAALAYAH, 2017)
The use of non-toxic and eco-friendly natural dyes on textiles has become a matter of significant importance because of the increased environmental awareness in order to avoid some synthetic dyes. Synthetic dyes are hazardous and carcinogenic and also release vast amount of pollutant in the environment during their manufacture and application, thus revival of natural dyeing techniques as one of the alternative is being emphasized for this purpose. Most effective ways for reducing environmental pollution is the replacement of polluting materials and chemicals by eco-friendly natural materials. Many natural resources which are being wasted indiscriminately or thrown away as a waste product contain useful dyes and pigments. In the present study, natural dye extracted from the waste leaves of Terminalia Catappa (tropical almond) and its application on silk fabrics pretreated with eco-friendly and non-eco-friendly mordants have been carried out successfully. Different shades with excellent to good fastness properties have been obtained.